A numerical modelling study of Port Alfred upwelling along the inshore edge of Agulhas current - Sunnassee, Taukoor Sheveenah (Department of Oceanography, 2025)
Port Alfred upwelling, located on the southeast African shelf, lies on the inshore edge of a western boundary current, the Agulhas Current. This study addresses the atmospheric and oceanographic forcing mechanisms responsible for these upwelling events through the daily simulations of a CROCO model of a horizontal spatial resolution of ~2.5km from 1993 to 2014. We tested several coastal upwelling indices and we identified 56 upwelling events from the residuals of sea surface temperature and 49 upwelling events through the decomposition of the vertical velocity. To assess the influence of the wind, we measured the alongshore wind stress, wind stress curl and frictional velocity at different temporal scales. Our analysis showed that upwelling during summer was primarily driven by northeasterlies inducing offshore Ekman transport and divergence. In contrast, stronger southwesterlies during winter could cause vertical mixing. To determine the Port Alfred upwelling’s driving mechanism during the mean state, we computed the terms of the generalized Ekman pumping equation and found that the advection of momentum contributed to 4.22 m/day of vertical velocity while the viscous flux term contributed partially to 0.5 m/day of vertical velocity. To determine whether the upwelling was driven by oceanographic mesoscale features (Agulhas Current, Natal pulses, Durban eddies, shear edge eddies and coastal trapped waves), we measured the sea surface height, geostrophic velocity, bottom Ekman transport and identified 1.9 large meander events annually from the LACCE current tracker algorithm, 2.2 based on eddy amplitude, 1.5 based on eddy area, and 1.3 based on eddy radius from the PY eddy tracker algorithm. We found that the Agulhas Current was the primary upwelling driver during the mean state, but some individual upwelling events were influenced by cyclonic eddies and coastal trapped waves. Finally, we conducted 2 combined Empirical Orthogonal Function analysis from (1) sea surface temperature and (2) vertical velocity and identified surface divergence as the most dominant upwelling driver in both combined EOFs while Ekman transport, the presence of cyclonic eddies, the Agulhas Current and coastal trapped waves also counted as contributing factors in stronger and weaker upwelling events. As an overall this study confirms that the Agulhas Current remains the primary upwelling driver during the mean state but through the lens of a different temporal scale (individual case studies and combined EOFs), it is likely that a combination of one or more forcing mechanisms (upwelling favourable winds, cyclonic eddy, Agulhas Current, coastal trapped waves) will trigger an upwelling event. Shedding more light on this topic and its main drivers allows oceanographers to focus more attention on this upwelling in the future and this could reinforce policymakers to consider Port Alfred upwelling region as a future Marine Protected Area.